Teaching Reading through Reciprocal Teaching Strategy - Afrizatama, Deni (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2016)
This  is  experimental  research  with  quantitative  approach  to  analyse  the  data. Quasi  experimental  is  used  to  gain  the  data  by  using  the  matching  only  pretest  – postest  control  group  design.Tne  main  ptirpose  of  tnis  researcn  was  intended  to  find out  whether  reciprocal  teaching  strategy  in  teaching  reading  for  the  eighth  grade  at SMPN 10 Kota Cirebon is effective or not and what the students’ response in learning reading using reciprocal teaching strategy are. In this research. The population of this research  was  eighth  grade  students  of  SMPN  10  Kota  Cirebon  in  the  2015/2016 academic year. The number population is about 270 students consisted of nine classes and each class consisted of 25  – 30 students.  This research only took two classes as sample,  VIII  H  as  control  class  and  VIII  I  as  experimental  class.  There  were  two research  instruments  that  was  used  to  gather  the  data:  Test  (Pre-test  and  Post-test) was used to find out the students’s achievement in reading before and after teaching reading by using reciprocal teaching strategy and questionnaire was used to find out the students’ response about learning reading using reciprocal teaching strategy. After collecting the data, the data was analyzed by using t-test formula from fraenkel to find out  t-account.  The  result  of  the  test  showed  that  t-account  was  4.47  and  t-table  was 2.012  with  (df)  48  and  significant  level  0.05  (5%).  It  means  that  t-account  (4.47)  is higher  than  t-table  (2.021).  It  can  be  concluded  that  (Ha)  “Reciprocal  teaching strategyis  effectivein  teaching  reading  for  the  eighth  grade  at  SMPN  10  Kota Cirebon.” is accepted.